Access to Pre-Primary Education and Progression in Primary School : Evidence from Rural Guatemala - Bastos, Paulo; Bottan, Nicolas L.; Cristia, Julian (World Bank, Washington, DC, 2016)
Evidence on the impacts of a large-scale expansion in pre-primary education is limited and mostly circumscribed to high- and middle-income nations. This study estimates the effects of such an expansion on progression in primary school in rural communities in Guatemala, where the number of pre-primary schools increased from about 5,300 to 11,500 between 1998 and 2005. Combining administrative and population census data in a difference-in-differences framework, the analysis finds that access to pre-primary education increased by 2.4 percentage points the proportion of students that progress adequately and attend sixth grade by age 12. These positive although limited effects suggest the need for complementary actions to produce substantial improvements in adequate progression.